2022
DOI: 10.3389/fnins.2022.848730
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cortical Volume and Thickness in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Myalgic Encephalomyelitis/Chronic fatigue syndrome (ME/CFS) patients suffer from neurocognitive impairment. In this study, we investigated cortical volumetric and thickness changes in ME/CFS patients and healthy controls (HC). We estimated mean surface-based cortical volume and thickness from 18 ME/CFS patients who met International Consensus Criteria (ICC) and 26 HC using FreeSurfer. Vertex-wise analysis showed significant reductions in the caudal middle frontal gyrus (p = 0.0016) and precuneus (p = 0.013) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…We observed a larger volume for the whole brainstem and pons in ME/CFS patients compared with HC. Previous studies in ME/CFS patients have reported lower mean diffusivity in the pons (Thapaliya et al, 2021), and higher T1/T2 signal intensity in the medial lemniscus and cortical spinal tract (Thapaliya et al, 2020) that is sensitive to the level of myelination or iron.…”
Section: Me/cfs Vs Hc Group Comparisonmentioning
confidence: 86%
See 2 more Smart Citations
“…We observed a larger volume for the whole brainstem and pons in ME/CFS patients compared with HC. Previous studies in ME/CFS patients have reported lower mean diffusivity in the pons (Thapaliya et al, 2021), and higher T1/T2 signal intensity in the medial lemniscus and cortical spinal tract (Thapaliya et al, 2020) that is sensitive to the level of myelination or iron.…”
Section: Me/cfs Vs Hc Group Comparisonmentioning
confidence: 86%
“…The symptom severity of ME/CFS was associated with brainstem dysfunction (Barnden et al, 2016). MRI studies showed lower mean diffusivity (Thapaliya et al, 2021), higher signal intensity (Barnden et al, 2018;Thapaliya et al, 2020), and impaired brainstem connectivity (Barnden et al, 2019) in the brainstem regions of ME/CFS patients. The brainstem regulates respiratory, cardiovascular, gastrointestinal, and neurological processes and its impairment can explain the overlapping symptoms of ME/CFS and long COVID.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Imaging studies in patients with ME have shown alterations in cortical and subcortical volumes, both positive and negative findings due to methodological variations [ 48 ]. A recent MRI study on cortical thickness and brain volumes found reduced cortical volumes and thickness in patients with ME compared with a healthy control group, and reductions correlated with fatigue [ 21 ]. Unlike these studies, we were not able to detect any differences between patients and controls neither in an extensive neuropsychological assessment covering different cognitive domains, nor in cortical thickness and brain volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The description of symptoms in PLDS resemble the description of myalgic encephalopathy (ME)/chronic fatigue syndrome, a condition also characterized by disabling fatigue, pain and malaise. Like PLDS, the etiology of ME remains unknown [ 19 ], and studies using quantitative MRI analysis on patients with chronic fatigue syndrome suggest alterations in grey and white matter [ 20 ], and reduced cortical volume and thickness in regions involved in attention, inhibition and memory retrieval [ 21 ].…”
Section: Introductionmentioning
confidence: 99%